Retrospective descriptive study "Jom Check Mata Malaysia" (JCM1M) / Rabia Tul Adawiyah Suhaimi - Suhaimi, Rabia Tul Adawiyah (2016)
Background: Vision screening in a primary care setting could be an effective way for early detection of eye disease. Although the usefulness of vision screening for the general public remains inconclusive, vision screening has been ascertained to be effective in at-risk patients. Aim: To analyze the vision screening outcomes based on retrospective data „Jom Check Mata 1 Malaysia (JCM1M)‟. Methods: This was a retrospective study of the results of vision screening during JCM1M. A retrospective review of 4,006 vision screening form between October 2012 and March 2014 was analyzed. The screening examination includes visual acuity measurement for both near and distance and ocular health screening by using ophthalmoscopy/ funduscopy and tonometry. These tests were carried out by optometry students UiTM Puncak Alam. The percentage and number were analyzed by using Microsoft Excel 2010. Results: Of 4,006 participants examined, 71% (n=2,843) passed the vision screening and 29% (n=1,163) failed the vision screening. The Southern region had the highest passing rate of about 95% (n=1,382) and the Eastern region had the lowest passing rate of about 50% (n=570). However, the urban areas still had the highest percentage of passed vision screening about 87% (n=1,755) as compared to the rural areas. Among them involved in vision screening, 72% (n=1,639) females passed vision screening and 67% (n=1,204) males passed vision screening. The elderly population had high failing rate, especially for those aged 61+. Conclusion: Vision screening pograms provide an important public health prevention opportunity to reach individuals who are less likely to receive a comprehensive eye examination. Screening programs also can offer a more affordable and accessible opportunity to evaluate those at risk for vision problems. Effective screening programs can lead to earlier treatments and a reduction in the overall burden of visual impairment. They also provide an opportunity to educate individuals on the importance of routine eye examinations and risks to vision health.